The Political Ethics of German Soccer Fans - Arne Koch; John Hanson (Acta Universitatis Carolinae Studia Territorialia)
This article investigates the complex interplay between soccer fandom and political activism in Germany, emphasizing fan groups’ emergence as significant political stakeowners. It explores the evolution of fan engagement from sports-specific to broader societal issues, illustrating how supporters articulate dissent against commercialization and advocate for ethical governance within clubs. Through representative examples of various clubs, from Stuttgart to Hamburg and from Frankfurt to Munich, this article highlights fans’ responses to controversial policies like Monday fixtures, the European Super League, and human rights violations. Utilizing sociologist Tim Crabbe’s analytical framework that approaches soccer culture via distinct contexts, this study critiques enduring assumptions about political homogeneity in fan behavior and examines how select groups navigate their identities as quasi-political entities. The findings suggest that German soccer fans increasingly challenge traditional notions of belonging, positioning themselves as active participants in club governance and wider societal debates. This analysis contributes to understanding the intricate relationship between soccer fandom, political activism, and club governance in Germany.